2010
DOI: 10.1016/s2255-4971(15)30443-2
|View full text |Cite
|
Sign up to set email alerts
|

Cuboid-Navicular Tarsal Coalition

Abstract: The authors present the case of a nine-year-old female patient who presented with pain in her right foot associated with physical activities. After this case was diagnosed as cuboid-navicular tarsal coalition, the patient was treated surgically with resection of the coalition, thereby resolving the symptoms. The literature was reviewed and the importance of adequate physical examination and imaging assessment for investigating foot pain in children and adolescents was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…A fourth case of incidental finding was described by Chu [24], after a pilon fracture, but it is unclear whether or not the patient was symptomatic from the coalition. Interestingly, these three asymptomatic patients [21][22][23] were in their forties (mean and median 45 years old), while symptomatic patients [16][17][18][19][20][25][26][27][28][29][30][31][32][33][34][35] were younger (mean age 23 years old, median 17 years old). The analysis of the cases of the literature for cubonavicular coalition revealed that symptoms were more frequent for nonosseous (14/16, 88%) than osseous (7/9 cases, 78%) union but the small number of cases does not allow any assertion.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth case of incidental finding was described by Chu [24], after a pilon fracture, but it is unclear whether or not the patient was symptomatic from the coalition. Interestingly, these three asymptomatic patients [21][22][23] were in their forties (mean and median 45 years old), while symptomatic patients [16][17][18][19][20][25][26][27][28][29][30][31][32][33][34][35] were younger (mean age 23 years old, median 17 years old). The analysis of the cases of the literature for cubonavicular coalition revealed that symptoms were more frequent for nonosseous (14/16, 88%) than osseous (7/9 cases, 78%) union but the small number of cases does not allow any assertion.…”
Section: Discussionmentioning
confidence: 99%
“…Talocalcaneal and calcaneo-navicular coalitions account for over 90% of cases and talo-navicular and calcaneo-cuboid coalitions for approximately 1% each. However, coalition between the cuboid and navicular is rare, with few reported cases in the literature [1,[5][6][7]. Conventional radiography is often sufficient for the diagnosis of more common tarsal coalitions, with a number of characteristic secondary radiographic signs described including the classical 'anteater nose' sign seen in calcaneo-navicular coalition.…”
Section: Discussionmentioning
confidence: 99%
“…Наявність аномальної кісткової, хрящової або фіброзної тканини між тарзальними кістками належить до прямої ознаки. Непрямі ознаки аналогічні рентгенологічним симптомам, описаним вище; вторинні запальні та дегенеративні зміни суміжних суглобів, набряк кісткової тканини [1,3,20]. Характерною виявилася непряма МР-ознака таранно-п'яткової коаліції -симптом «п'яного офіціанта» («drunken waiter») (рис.…”
Section: рисунок 4 комп'ютерна томограма пацієнта з таранно-п'ятковою тк (а) та п'ятково-човноподібною тк (б) у корональній проєкції рисуunclassified
“…Згідно з МКХ-10, займає позицію Q66.8: Інші вроджені деформації стопи. Поширеність патології, за даними різних авторів, становить від 1 до 13 % усієї популяції [2,3]. Доведений автосомно-домінантний тип успадкування з високою пенетрантністю ознаки [4].…”
unclassified
See 1 more Smart Citation